PENINGKATAN MUTU PEMBELAJARAN MELALUI SUPERVISI AKADEMIK BERBASIS LESSON STUDY - Tuti Sundari (Equity In Education Journal, 2023)
This research is a school action research that emphasizes the implementation of supervision which is integrated in Lesson study activities This research is collaborative involving participants joining together to observe the learning process in understanding learning and changes in activity due to the actions given. Objectives To improve students' understanding and learning activities through the development of inquiry learning which is applied in lesson study. The data collection technique used is descriptive qualitative from observations of lesson study activities resulting from observations of questionnaires for teachers and students. The implementation of supervision that is integrated in lesson study activities is capable of developing inquiry-based learning which refers to improving learning outcomes and finding more improvements in the next learning process. Improving students' understanding and learning activities through the development of inquiry-based learning which is applied in lesson study fosters a sense of more fun in learning.